Transformation of cash waqf management in Indonesia: Insights into the development of digitalization - Hendri Hermawan Adinugraha; Muhammad Shulthoni; Zohaib Hassan Sain (Review of Islamic Social Finance and Entrepreneurship)
Purpose – This study intends to provide an in-depth explanation of the importance of transforming cash waqf management in Indonesia through a digitalization platform. Methodology – This research was library research. The data collection techniques used in this study were literature review and documentation. Data analysis techniques are in the form of content analysis. The stages of content analysis in this research were carried out by determining the problem, compiling a framework of thought, compiling methodological tools, analyzing literature data, and interpreting the data that have been obtained. Findings – The findings of this study suggest that cash waqf innovation through digital platforms has proven to be an applicable solution. The transformation of cash waqf management through digital platforms has proven to accelerate the growth of waqf assets and the benefits of waqf for the improvement of community welfare and to increase public knowledge and awareness of cash waqf. The constraints of digital cash waqf development in Indonesia are the lack of qualified and professional nazirs and human resources, strong business network for digital cash waqf development, digital cash waqf socialization among the public, and popularity of digital waqf institutions. Implications – This research is useful for improving the transformation of cash waqf management through digitalization, which has demanded collaboration and synergy between the Indonesian government and Zakat institutions. Originality – This study examined the digital transformation model of cash waqf management in Indonesia.